Cytosolic double-stranded RNA activates the NLRP3 inflammasome via MAVS-induced membrane permeabilization and K+ efflux - Franchi, Luigi; Eigenbrod, Tatjana; Muñoz-Planillo, Raúl; Ozkurede, Ulas; Kim, Yun-Gi; Chakrabarti, Arindam; Gale, Michael; Silverman, Robert H.; Colonna, Marco; Akira, Shizuo; Núñez, Gabriel (The journal of immunology, 2014)
The nucleotide-binding oligomerization domain-like receptor pyrin domain-containing 3 (Nlrp3) inflammasome plays an important role in inflammation by controlling the maturation and secretion of the cytokines IL-1β and IL-18 in response to multiple stimuli including pore-forming toxins, particulate matter, and ATP. Although the pathways activated by the latter stimuli lead to a decrease in intracellular K+ concentration, which is required for inflammasome activation, the mechanism by which microbial RNA activates Nlrp3, remains poorly understood. In this study, we found that cytosolic poly(I:C), but not total RNA from healthy macrophages, macrophages undergoing pyroptosis, or mitochondrial RNA, induces caspase-1 activation and IL-1β release through the Nlrp3 inflammasome. Experiments with macrophages deficient in Tlr3, Myd88, or Trif, indicate that poly(I:C) induces Nlrp3 activation independently of TLR signaling. Further analyses revealed that the cytosolic sensors Rig-I and melanoma differentiation-associated gene 5 act redundantly via the common adaptor mitochondrial antiviral signaling (Mavs) to induce Nlrp3 activation in response to poly(I:C), but not ATP or nigericin. Mechanistically, Mavs triggered membrane permeabilization and K+ efflux independently of the inflammasome which were required for poly(I:C)-induced Nlrp3 activation. We conclude that poly (I:C) activates the inflammasome through an Mavs-dependent surveillance pathway that converges into a common K+ lowering step in the cytosol that is essential for the induction of Nlrp3 activation.
Gesehen am 08.07.2020